Education in Malaysia: building global citizens / Fatin Aliyah Hassan ... [et al.] - Hassan, Fatin Aliyah (Universiti Teknologi MARA, Negeri Sembilan, 2024)
The importance of global education cannot be overstated in today’s interconnected world. It equips students with the values, skills, and abilities to navigate and participate in a complex, interdependent society. Global education is also important because it promotes cultural awareness and social responsibility among Malaysian students, a country noted for its cultural diversity. This results in informed and compassionate global citizens. Global education encompasses various aspects of life, including cultural awareness, critical thinking, global awareness, social responsibility, and collaboration. Therefore, exposing students to diverse cultures and global issues prepares them to become active and responsible global citizens and broadens their perspectives on life.